2002
DOI: 10.4049/jimmunol.169.5.2648
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiological Contributions of Fucosyltransferases in Renal Ischemia Reperfusion Injury

Abstract: Ischemia reperfusion injury (IRI) is a major cause of delayed graft function. Recent studies have shown that selectins play an important role in IRI. Selectins bind to sialylated and fucosylated sLex receptors, and two enzymes, fucosyltransferase IV (FucT-IV) and VII (FucT-VII), are important in the function of these receptors. We hypothesized that fucosyltransferase (FucT) enzymes were important pathophysiologic mediators of renal IRI. We therefore evaluated renal IRI in mice deficient in FucT-IV, FucT-VII, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 24 publications
(35 reference statements)
0
12
0
Order By: Relevance
“…Leukocyte rolling is mediated by a class of adhesion molecules known as selectins (Lasky 1992), which bind to sialylated and fucosylated oligosaccharide antigens such as Le x and sLe x . Regulated specific expression of the a1,3 fucosyltransferases responsible for fucosylation controls the expression of these antigens (Burne & Rabb 2002). Leukocyte homing was eliminated in mice that lack both FUT4 and FUT7 (Homeister et al 2001).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Leukocyte rolling is mediated by a class of adhesion molecules known as selectins (Lasky 1992), which bind to sialylated and fucosylated oligosaccharide antigens such as Le x and sLe x . Regulated specific expression of the a1,3 fucosyltransferases responsible for fucosylation controls the expression of these antigens (Burne & Rabb 2002). Leukocyte homing was eliminated in mice that lack both FUT4 and FUT7 (Homeister et al 2001).…”
Section: Discussionmentioning
confidence: 93%
“…In addition, data from Weninger et al (2000) showed that FUT4 is crucial for the selectinmediated slow rolling of leukocytes on endothelial cells. FUT4 was the first leukocyte-associated enzyme linked to selectin ligand synthesis (Goelz et al 1990, 1994, Burne & Rabb 2002, such as Le The similarities between leukocyte rolling on endothelial cells and the initial stages of blastocyst attachment to the endometrial epithelium in humans have been recognized in recent years (Genbacev et al 2003, Dominguez et al 2005. The L-selectin system has also been shown to be important in the initial contact of the trophoblast to the luminal epithelium of human endometrium.…”
Section: Discussionmentioning
confidence: 99%
“…Blockade of the shared ligand to all three selectins (E-, P-, and L-selectin), which appears to be dependent on the presence of a key fucosyl sugar on the selectin ligand, led to reduced injury and mortality. Further, mice genetically deficient for E-selectin or P-selectin or both were completely protected in the cecal ligation and puncture model (CLP), a preclinical model for sepsis (88,89).…”
Section: Endotheliummentioning
confidence: 99%
“…We used murine models in which the structural and functional consequences of brief periods of renal ischemia have been documented (11)(12)(13)(14)(15). The characteristic histopathologic features of ischemic injury were readily evident in the 24-h reperfusion samples after both unilateral (45 min) and bilateral (30 min) ischemia.…”
Section: Characterization Of the Animal Models Of Early Renal Ischemimentioning
confidence: 99%
“…We used well-established murine models in which the structural and functional consequences of brief periods of renal ischemia have been previously documented (11)(12)(13)(14)(15). Briefly, male Swiss-Webster mice (Taconic Farms, Germantown, NY) weighing 25 to 35 g were housed with 12:12-h light:dark cycle and were allowed free access to food and water.…”
Section: Mouse Models Of Renal Ischemia-reperfusion Injurymentioning
confidence: 99%